Culturas de inverno no manejo de fitonematoides e no desempenho agronômico da cultura do milho no Noroeste do Paraná - Chiamolera, Fernando Marcelo (2012)
In the different agricultural systems, rotation or succession crops should be considered as one of the main alternatives for managing phytonematodes, since, besides promoting populations reduction of these pathogens, deployed crops may be used as green fertilizers on nitrogen fixation or as mulch, improving chemistry, physics and biological conditions of soil. However, literatures are scarce aiming to study the susceptibility of temperate climate crops in Arenito Caiua conditions. Thus, the present work objectifyed to evaluate the effect of winter crops, under two sources of fertilizer over Pratylenchus brachyurus, Helicotylenchus spp. and Meloidogyne spp. populations, in sandy texture soil, naturally infested and over production components relationed to maize crop yield, in area with a history of five years in succession soybean / black oat under direct seeding system in the North western region of Parana State. For the experiment in Field conditions, it was observed that black oat, fodder radish, and their consortium promoted better control of P. brachyurus. Besides it, inferior populations of studied phytonematodes were observed with organic fertilization through the application of poultry manure. After maize cultivation in summer season and off-season there was suppression of Meloidogyne spp. and elevation in populations of P. brachyurus and Helicotylenchus spp., however, on smaller levels in relation to the initial population diagnosed. Under controlled conditions, the largest reproduction of P. brachyurus was observed to lodging, bean and grass pea, while the smallest ones were obtained for black oat and fodder radish, confirming the observed results in Field conditions. On the evaluation of production components of maize crop, in summer season, the succession vetch/maize, and in off-season vetch/maize and bean/maize successions fertilized with poultry manure, showed to be agricultural useful for maize grain production, joint to nutritional and phytossanitary management adequated of the crop, employing hidric supplement.